Between scientific literacy and letramento: discursive disputes and the construction of meaning in the language of science education in Brazil - Darque de Souza, Raimunda (2025)
The article analyzes the meanings attributed to the terms scientific literacy and scientific ‘letramento’ within the context of Brazilian education, highlighting their different appropriations in academic literature and curriculum policies. Based on a critical review of recent studies and official documents such as the National Curriculum Parameters (1998), the National Curriculum Guidelines (2010), and the Common National Curriculum Base (2017–2018), we examine how these concepts have been redefined according to divergent pedagogical and political projects. Scientific literacy is consolidated in public policies as a functional category, oriented toward the acquisition of assessable content and competencies. However, ‘scientific letramento’ is presented in academic literature as a situated social practice, articulated with language, citizenship, and critical thinking. The text brings together national and international authors, review studies, and document analysis. In some cases, Discourse Analysis is used as an interpretive tool to understand the effects of meaning and silences in curriculum texts. It is concluded that the dispute between the two terms reflects different conceptions of science, language, subject, and education. It is suggested that future studies investigate how these concepts are appropriated by teachers in contexts marked by inequality and cultural diversity.